2014
DOI: 10.6065/apem.2014.19.3.141
|View full text |Cite
|
Sign up to set email alerts
|

Earlier re-evaluation may be possible in pediatric patients with eutopic congenital hypothyroidism requiring lower L-thyroxine doses

Abstract: PurposeThe incidence of congenital hypothyroidism (CH) has increased in several countries. Lower cut-off in screening programs have led to an increase in the proportion of transient hypothyroidism (TH) cases diagnosed, leading to debate on the associated clinical and economic impact. This study aimed to identify factors that would allow discrimination between TH and permanent CH (PH) in patients with a eutopic thyroid gland.MethodsSixty-six patients with CH from 3 different hospitals were studied: 26 cases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
38
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 21 publications
11
38
5
Order By: Relevance
“…This study suggests that abnormal thyroid imaging study, needs to escalate the thyroxine dosage for adjusting normal TFT during follow up, positive anti-thyroid antibody, high TSH and low FT4 levels at initial test ( the exact value is not determined, yet), CH rather than persistent HTT are the significant risk factor for PHT. Some of our study's findings are consistent with the previous studies [24][25][26][27]. Moreover, it is possible that infants who had no or fewer risk factors mentioned before are candidates for early trial off-therapy [29,30].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study suggests that abnormal thyroid imaging study, needs to escalate the thyroxine dosage for adjusting normal TFT during follow up, positive anti-thyroid antibody, high TSH and low FT4 levels at initial test ( the exact value is not determined, yet), CH rather than persistent HTT are the significant risk factor for PHT. Some of our study's findings are consistent with the previous studies [24][25][26][27]. Moreover, it is possible that infants who had no or fewer risk factors mentioned before are candidates for early trial off-therapy [29,30].…”
Section: Discussionsupporting
confidence: 82%
“…Of course, it is not known how many of these children required continued treatment or experience adverse effects from discontinuation. Therefore, in the meantime, there have been many efforts to predict the permanence of thyroid dysfunction [24][25][26][27][28]. This study suggests that abnormal thyroid imaging study, needs to escalate the thyroxine dosage for adjusting normal TFT during follow up, positive anti-thyroid antibody, high TSH and low FT4 levels at initial test ( the exact value is not determined, yet), CH rather than persistent HTT are the significant risk factor for PHT.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that infants with CH requiring lower L-thyroxine doses (<3.25 µg/kg) are likely to have transient CH, and thus might be re-evaluated at 12 or 24 months rather than 3 years of age (57). There is a critical necessity for specific guidelines regarding the follow-up and reevaluation of transient CH, especially in preterm babies.…”
Section: Evidence Not To Treat Thopmentioning
confidence: 99%
“…29,30 Outcome Factors known to influence the neurodevelopmental outcome in children with CH are the age at initiation of treatment, starting dose of levothyroxine, severity of hypothyroidism, serum T4 concentrations in the first 2 years of life, and compliance to therapy 23 . The dose and timing of levothyroxine therapy are crucial to the neurologic outcome in CH.…”
Section: Recommended Follow Upmentioning
confidence: 99%